State of the art on biodegradability of bio-based plastics containing polylactic acid - Lors, Christine; Leleux, Pauline; Park, Chung Hae (Frontiers in Materials, 2025)
Bio-based plastics represent an opportunity to reduce the impact of petroleum-based plastics on the environment, leading to harmful effects on both terrestrial and marine ecosystems. Nevertheless, the plant origin of bio-based plastics does not necessarily imply better management of their end of life. However, when recycling is impossible, the biological degradation of bio-based plastics would be an effective method to reduce their environmental impact. Polylactic acid (PLA) is one of the most produced biopolymers currently among the bio-based plastics already developed for several years. Thus, the objective of this article is to provide a state of the art on the biodegradation of bio-based plastics based on PLA. In particular, the microorganisms catalyzing the different biochemical reactions and the main biodegradation mechanisms are reviewed according to aerobic and anaerobic conditions. Moreover, different microorganisms involved in the degradation of PLA are summarized. Furthermore, a special attention is paid to the analytical methods to evaluate the biodegradation of polylactic acid and to the different existing biodegradation test methods, because this subject has rarely been reviewed in the literature. In the end, several promising topics for the future research are proposed, such as enzyme engineering technology as a recently emerging method for PLA degradation and a new common testing method to collect as much data as possible on the biodegradability to compare different studies.